All the wrong moves : a memoir about chess, love, and ruining everything - Chapin, Sasha (Doubleday, 2019)
"A globe-trotting romp through the world of ultra-competitive chess, in which the author submits himself to humiliating defeats and the tutelage of ornery mentors in his search for glory--a celebration of the purity, violence, and beauty of the game"--